ChemInform Abstract: Synthesis of Substituted Picenes Through Pd‐Catalyzed Cross‐Coupling Reaction/Annulation Sequences and Their Physicochemical Properties. Issue 49 (3rd December 2013) - Chang, Ning‐hui; Chen, Xi‐chao; Nonobe, Hikaru; Okuda, Yasuhiro; Mori, Hiroki; Nakajima, Kiyohiko; Nishihara, Yasushi
Abstract A two step sequence involving Suzuki—Miyaura coupling of halobenzene (I) with boronates (II) and subsequent intramolecular double cyclization provides picenes (IV) in low to moderate yields.